The Long March in the New Era - Qinxuan Peng (Journal of Southeast Asian Human Rights, 2019)
China has entered a New Era with an aspiration to safeguard human rights through law. However, implementation gaps are found when comparing the current Chinese domestic laws on non-discrimination with the requirements set by international human rights treaties and international labour standards on eliminating discrimination in the labour market. This article illustrates how rural migrant workers are an underprivileged group in Chinese society, emphasising the inferior treatment they experience due to their agricultural hukou residential status in urban areas. The study identifies several implementation gaps between the international standards and the Chinese domestic legal system on non-discrimination, serving as the very first step to eradicate de facto and de jure discrimination and to achieve Legal Protection of Human Rights in the New Era.